USING HEURISTIC STRATEGIES TO PROMOTE MATHEMATICS PROBLEM SOLVING ABILITY OF GRADE 10 STUDENTS - Vongyai, Attakan; Noparit, Tipparat (PEOPLE: International Journal of Social Sciences, 2019)
The main purposes of the research were to investigate how to teach Heuristic strategies to promote students solving the problem, and to study the ability of tenth grade students who had been taught to solve mathematic problems by utilizing the Heuristic method. The target group consisted of 47 grade 10 students at Wattanothai Payap school, Chiang Mai Province, Thailand. The researcher conducted classroom action research with 3 cycles. Instruments included lesson plans, students’ written work, and the problem-solving ability test. Data was analyzed by frequency, percentage, and content analysis. The results showed that 1) The teaching approach utilizing Heuristic strategies used in this research consisted of the following steps: the teacher encouraged the students to experiment by using their own strategies, then challenged them to utilize the complicated strategies, Guess-check-revise, Systematic experimentation (making a table, equation), and Use of graph of function. 2) Results from the test showed that 35 students of the 47 students (74.46%) passed the criteria (70% of total score). The strategies most students used were Systematic experimentation, and Guess-check-revise, and Use of graphs of function, respectively. From the results, the researcher learned that the key success factors that made students dare to solve problems, were to give them more tools to use and more opportunities to learn from each other. Students were able to freely choose their own way to solve problems without any fear.